2023
DOI: 10.3390/rs15082212
|View full text |Cite
|
Sign up to set email alerts
|

TPENAS: A Two-Phase Evolutionary Neural Architecture Search for Remote Sensing Image Classification

Abstract: The application of deep learning in remote sensing image classification has been paid more and more attention by industry and academia. However, manually designed remote sensing image classification models based on convolutional neural networks usually require sophisticated expert knowledge. Moreover, it is notoriously difficult to design a model with both high classification accuracy and few parameters. Recently, neural architecture search (NAS) has emerged as an effective method that can greatly reduce the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Hence, the results of this research could be discussed with respect to studies carried out in forests of different growing stages. An improvement of the OA of species classification between 1-4.3 pp was documented in mature forests by hybridizing the CNN and k-nearest neighbors [54], combining Res-Net and U-net structures [55], using their proposed 3D-1D-CNN method [56], and using a novel two-phase CNN [57]. Hence, the magnitude of improving the OA of classifying seedlings in this study was in line with the aforementioned literature of mature forests.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the results of this research could be discussed with respect to studies carried out in forests of different growing stages. An improvement of the OA of species classification between 1-4.3 pp was documented in mature forests by hybridizing the CNN and k-nearest neighbors [54], combining Res-Net and U-net structures [55], using their proposed 3D-1D-CNN method [56], and using a novel two-phase CNN [57]. Hence, the magnitude of improving the OA of classifying seedlings in this study was in line with the aforementioned literature of mature forests.…”
Section: Discussionmentioning
confidence: 99%
“…(2022a) proposed a new CNN consisting of a group of so-called self-compensating convolutional modules. Ao et al. (2023), Broni-Bediako et al.…”
Section: Related Workmentioning
confidence: 99%
“…E.g., Shi et al (2022a) proposed a new CNN consisting of a group of so-called self-compensating convolutional modules. Ao et al (2023), Broni-Bediako et al (2022 and Shen et al (2022a, b) proposed three CNN architectures obtained by neural architecture search. Speaking of advantages, these four methods both have fewer parameters compared to the off-theshelf CNNs developed on ImageNet-1K.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, applying NAS to RSI data sets could yield more efficient deep models that leverage general RSI features. However, existing NAS studies (Ao et al , 2023; Broni-Bediako et al , 2022; Shen et al , 2022a) have only validated their models on RSI data sets significantly smaller than ImageNet-1K. Consequently, these NAS-based models have demonstrated smaller volumes without achieving competitive accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…Alternatively, custom-built CNN architectures developed through neural architecture search (NAS) on RSI data sets may offer improved solutions. For instance, Ao et al (2023), Broni-Bediako et al (2022) and Shen et al (2022a) proposed their NAS-based CNNs and demonstrated much smaller volumes than preexisting models. However, these NAS-based methods still achieved significantly lower accuracy because the NAS was only performed on RSI data sets with several tens of thousands of data points.…”
Section: Introductionmentioning
confidence: 99%